The effect of hyperthyroidism on procoagulant, anticoagulant and fibrinolytic factors - Stuijver, Danka J.F.; Zaane, Bregje van; Romualdi, Erica; Brandjes, Dees P.M.; Gerdes, Victor E.A.; Squizzato, Alessandro (Thrombosis and Haemostasis, 2012)
Several coagulation and fibrinolytic parameters appear to be affected by thyroid hormone excess;however, the net effect on the haemostatic system remains unclear. We aimed to update our previous review and systematically summarise and meta-analyse the data by assessing the effects of thyrotoxicosis on the coagulation and fibrinolytic system in vivo. Data sources included MEDLINE (2006–2012), EMBASE (2006–2012), and reference lists. The sources were combined with our previous search containing studies from 1980–2006. Eligible studies were all observational or experimental studies. Two investigators independently extracted data and rated study quality. Weighted mean proportion and 95% confidence intervals were calculated and pooled using a fixed and a random-effects model. A total of 29 articles consisting of 51 studies were included, as in several articles more than one study was described. We included four intervention (before and after treatment in hyperthyroid patients), five cross-sectional (hyperthyroid subjects and euthyroid controls), and four experimental (before and after use of thyroid hormone in euthyroid subjects) medium/high quality studies for meta-analysis. We found that thyrotoxicosis shifts the haemostatic balance towards a hypercoagulable and hypofibrinolytic state with a rise in factors VIII and IX, fibrinogen, von Willebrand factor, and plasminogen activator inhibitor-1. This was observed in endogenous and exogenous thyrotoxicosis, and in subclinical as well as overt hyperthyroidism. We conclude that both subclinical and overt hyperthyroidism induce a prothrombotic state, which is therefore likely to be a risk factor for venous thrombosis.
Keywords: Thyrotoxicosis; Hyperthyroidism; Coagulation; fibrinolysis